Soft metal constructs for large strain sensor membrane - Michaud, Hadrien O; Teixidor, Joan; Lacour, Stéphanie P (Smart materials and structures, 2015)
Thin gold films on silicone display large reversible change in electrical resistance upon stretching. Eutectic liquid metal conductors maintain bulk metal conductivity, even upon extensive elongation. When integrated together, the soft metals enable multidirectional, large strain sensor skin. Their fabrication process combines thermal evaporation of thin gold film patterns through stencil mask with microplotting of eutectic gallium indium microwires, and packaging in silicone rubber. Using three-element rectangular rosettes, we demonstrate a sensor skin that can reliably and locally quantify the plane strain vector in surfaces subject to stretch (up to 50% strain) and indentation. This hybrid technology will find applications in soft robotics, prosthetics and wearable health monitoring systems.